Experimental and analytical investigation on flexural behaviour of ambient cured geopolymer concrete beams reinforced with steel fibers - Tran, Tung; Pham, Thong; Hao, Hong (ELSEVIER SCI LTD, 2019)
This study investigates the flexural behaviour of geopolymer concrete (GPC) beams reinforced with steel fibers. The effects of the volume fraction and fiber length on the flexural behaviour of GPC beams are investigated. The distinctive behaviour of GPC beams versus ordinary Portland Concrete (OPC) beams is identified and discussed. Based on the experimental results, the GPC beams reinforced with steel fibers showed great improvement in the cracking resistance, serviceability, and ductility compared to the reference beams. The GPC beam without steel fibers failed in a very brittle manner while those reinforced with steel fibers experienced ductile failure. The load capacity of the GPC beams increased with the volume fraction of steel fiber up to 0.75%. Further increasing the fiber content to 1.5% showed a deterioration in the flexural behavior due to poor workability of GPC leading to worse fiber dispersion and orientation. The increase of fiber length up to 60 mm did not improve the moment capacity of the GPC beams owing to premature fiber fracture. An analytical procedure was proposed to estimate the load-deflection curve of the tested beams with good correlation between predictive and experimental results.